Toward a Version of China: The Taiwan Experience - Yaofu, Lin (Surfaces, 1995)
This essay elucidates the components and modalities of Taiwan's cultural identity. In describing this cultural identity, which includes issues of literature and language as well as of collective self-understanding, it characterizes the context of Taiwan's social, political, and cultural history, particularly with regard to China but also in reference to Japan.